Two new species of the genus Acrossus Mulsant, 1842 (Scarabaeidae: Aphodiinae) closely related to Acrossus ritsemae (Schmidt, 1909). (3rd April 2018) - Minkina, Łukasz
Abstract: Two new species of the genus Acrossus Mulsant, 1842 from China are described and illustrated: Acrossus byki sp. nov., and A. jeloneki sp. nov. Both species are closely related to Acrossus ritsemae (Schmidt, 1909) from India and Nepal. The new species are described, illustrated and compared with A. ritsemae (Schmidt, 1909). Additionally, A. ritsemae (Schmidt, 1909) is reported from China for the first time. http://www.zoobank.org/urn:lsid:zoobank.org:pub:1F2446DB-9764-4157-AAC7-081C2B7B6F4E